Two-step enzymatic synthesis of 6-deoxy-l-psicose. Issue 34 (24th August 2016) - Wen, Liuqing; Huang, Kenneth; Zheng, Yuan; Fang, Junqiang; Kondengaden, Shukkoor Muhammed; Wang, Peng George
Graphical abstract: Highlights: An enzyme that specifically recognizes 6-deoxy-l -psicose was identified. One-pot multienzyme system was used to convertl -rhamnose to 6-deoxy-l -psicose. Product was obtained with high yield and purity without isomer separation step. Abstract: Rare sugars offer a plethora of applications in the pharmaceutical, medicinal, and industries, as well as in synthetic chemistry. However, studies of rare sugars have been hampered by their relative scarcity. In this work, we describe a two-step strategy to efficiently and conveniently prepare 6-deoxy-l -psicose froml -rhamnose. In the first reaction step, the isomerization ofl -rhamnose (6-deoxy-l -mannose) tol -rhamnulose (6-deoxy-l -fructose) catalyzed byl -rhamnose isomerase (RhaI), and the epimerization ofl -rhamnulose to 6-deoxy-l -psicose catalyzed byd -tagatose 3-epimerase (DTE) were coupled with selective phosphorylation reaction by fructose kinase from human (HK), which selectively phosphorylate 6-deoxy-l -psicose at C-1 position. 6-deoxy-l -psicose 1-phosphate was purified by a silver nitrate precipitation method. In the second step, the phosphate group of the 6-deoxy-l -sorbose 1-phosphate was hydrolyzed with acid phosphatase (AphA) to produce 6-deoxy-l -psicose in 81% yield with respect tol -rhamnose. This method allows that the 6-deoxy-l -psicose to be obtained from readily available starting materials with high purity and without having to undergo isomer separation.